2000
DOI: 10.3168/jds.s0022-0302(00)75019-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Gain in Pre- and Postpubertal Replacement Dairy Heifers on Body Condition Score, Body Size, Metabolic Profile, and Future Milk Production

Abstract: Two trials were conducted to evaluate the effect of moderate (0.7 kg) and accelerated (0.9 kg) average daily gain before (trial 1) and after (trial 2) puberty on body condition, metabolic profile, and first lactation milk production of Italian Holstein-Friesian heifers. There were 20 heifers in trial 1 and 22 in trial 2. Trials started when heifers averaged 150 and 300 kg of body weight in trial 1 and 2, respectively, and lasted 7 mo (experimental period). Across diet groups, half of the heifers were mated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
1
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 18 publications
13
56
1
7
Order By: Relevance
“…Interestingly, the variation in milk solids production was driven by differences in volume rather than differences in composition. These findings are in line with the studies of Gardner et al (1988), Abeni et al (2000) and Dobos et al (2001), who all showed a positive relationship between BW at first calving and subsequent milk production performance. In contrast, Macdonald et al (2005) found that BW at first calving is important for first lactation milk production, but its effect diminished in subsequent lactations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the variation in milk solids production was driven by differences in volume rather than differences in composition. These findings are in line with the studies of Gardner et al (1988), Abeni et al (2000) and Dobos et al (2001), who all showed a positive relationship between BW at first calving and subsequent milk production performance. In contrast, Macdonald et al (2005) found that BW at first calving is important for first lactation milk production, but its effect diminished in subsequent lactations.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Hoffman and Funk (1992) documented that research efforts to reduce the age at first calving below 22 to 24 months of age have generally resulted in reduced milk yield. Abeni et al (2000) reported that milk fat concentration was decreased when age at first calving was reduced, whereas other studies have found that protein percentage was higher (Pirlo et al, 1997) with an earlier calving date. Extending age at first calving beyond 750 days of age was found not to improve the performance of primiparous cows, and the highest economic return was observed when cows first calved between 700 and 740 days of age (Ettema and Santos, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies have reported the mean number of services per conception for HolsteinFriesian heifers at spontaneous oestrus as 1.5 (Abeni et al, 2000;Taylor et al, 2003), and at synchronised oestrus as 2.1 (Carson et al, 2002). In the present study, the mean number of three services given to heifers that failed to conceive before the decision was made to cull them was similar to previous findings for infertile heifers (Taylor et al, 2003;Wathes et al, 2007).…”
Section: Discussionsupporting
confidence: 80%
“…At the same time, the body condition score of each heifer was assessed according to our previous research (Abeni et al, 2000).…”
Section: Animals Diets Ingredients and Trial Managementmentioning
confidence: 99%